Front Cover: Time Resolved in situ DXAFS Revealing Highly Active Species of PdO Nanoparticle Catalyst for CH4 Oxidation (ChemCatChem 16/2018). Issue 16 (30th August 2018) - Mahara, Yuji; Murata, Kazumasa; Ueda, Kakuya; Ohyama, Junya; Kato, Kazuo; Satsuma, Atsushi
Abstract : The Front Cover shows energy dispersive X‐rays illuminating a PdO nanoparticle reduced by methane. In their Communication, Y. Mahara et al. used time‐resolved in situ dispersive XAFS for the kinetic analysis of the reduction of PdO nanoparticles, which led to partial formation of Pd 0 that accelerates methane combustion. More information can be found in the Communication by Y. Mahara et al. onpage 3384 in Issue 16, 2018 (DOI:10.1002/cctc.201800573 ).